Risk factors and clinical effects of subclinical leaflet thrombosis after transcatheter aortic valve replacement - Bak, Minjung; Park, Sung-Ji; Choi, Kihong; Kim, Jihoon; Park, Taek Kyu; Kim, Eun Kyoung; Kim, Sung Mok; Choi, Seung-Hyuk (Frontiers in Cardiovascular Medicine, 2022)
Aims The number of trans-catheter aortic valve replacement (TAVR) procedure is increasing; However, the incidence of leaflet thrombosis is higher in TAVR than in surgical aortic valve replacement (SAVR). In this study, the risk factors for leaflet thrombosis after TAVR and its effects on hemodynamics and clinical course were investigated. Methods and results Multidetector computed tomography (MDCT) was performed at 1year after TAVR in 94 patients from January 2015 to October 2020 at Samsung Medical Center in South Korea. Among the 94 patients, subclinical leaflet thrombosis occurred in 20 patients, and risk factors were analyzed. In addition, the difference in aortic valve (AV) hemodynamics between the two groups was examined and clinical outcomes compared. Indexed mean sinus of Valsalva (SOV) diameter, AV calcium volume, and post-procedure effective orifice area (EOA) were predictive of subclinical leaflet thrombosis with the area under the curve (AUC) value of 0.670 (P-value = 0.020), 0.695 (P-value = 0.013), and 0.665 (P-value = 0.031), respectively. In echocardiography performed at the time of follow-up CT, the value of AV max velocity and AV mean pressure gradient were higher in the thrombosis group and the EOA and Doppler velocity index values were lower in the thrombosis group than in the no thrombosis group. Clinical outcome was not significantly different between the two groups (log-rank P-value = 0.26). Conclusion Larger indexed SOV diameter, higher AV calcium volume, and smaller post-procedure AV EOA were risk factors for subclinical leaflet thrombosis after TAVR. Subclinical leaflet thrombosis has a benign course when properly managed.